Soybean in the etate of Maranhão, Brazil: a temporal analysis of expansion and substitution of food crops - Feitosa, Milena Monteiro; Sousa, Erika Costa; Nascimento, Louize; Lemos, José de Jesus Sousa (Geografares, 2023)
Brazil is a prominent global producer of soybeans, which rank among the most commonly produced and consumed grains worldwide. In Maranhão, a state located within Brazil’s agricultural frontier, called MATOPIBA, region that includes parts of the states of Maranhão, Tocantins, Piauí and Bahia, 135 out of 217 municipalities have experienced an increase in grain production. The objective of this study is to examine the spatial and temporal patterns of soybean farming expansion over areas that formerly grew rice, beans, cassava, and corn in the Maranhão state region. To achieve this objective, the research used data from the Agricultural Production of Municipalities of the Brazilian Institute of Geography and Statistics and the Getúlio Vargas Foundation from several years. Over the past 40 years, soybean growing has expanded its production in the municipalities comprising that frontier, as indicated by the findings. The study concludes that soybean cultivation in the municipalities of MATOPIBA, Maranhão, has expanded into previously unexploited areas. In particular, it has occupied parts of land previously used for other crops.